Changes of hyoid bone position following treatment of class II div1 malocclusion with Farmand functional appliance - Yassaei S; Soroush MM (Tehran University of Medical Sciences, 2007)
Background and Aim: Unlike other bones of the head and neck, hyoid bone has no bony articulations. It is connected to mandible, cranium and pharynx through muscles and ligaments. During treatment with functional appliance in patients with class II div1 malocclusion, mandible is positioned in inferior and anterior direction. Regarding the relation between hyoid and mandibular bone, alterations of hyoid bone position can be a result of functional appliance therapy. The aim of this study was to evaluate the changes of hyoid bone position following treatment with Farmand functional appliance in patients with class II div 1 malocclusion. Materials and Methods: In this before-after clinical trial, 28 patients with class II div 1 malocclusion which were under treatment with Farmand functional appliance for 11 months were selected. Facial growth in vertical, normal or horizontal direction was determined by cephalometric measurement. Data were analyzed with Paired-t test to compare the differences of mean values pre and post treatment. Variance analysis was used to compare the three growth patterns. P<0.05 was considered as the limit of significance. Results: Hyoid bone shifted significantly forward in horizontal dimension (P<0.01) and non-significantly upward in vertical dimension. There was no significant difference among the three studied groups with respect to hyoid bone position alterations in horizontal dimension but significant difference was observed between horizontal and vertical growth pattern in vertical dimension (P<0.05). There was significant correlation between decrease of ANB angle and forward movement of hyoid bone. Conclusion: Based on the results of this study, treatment with Farmand functional appliance (Fa II) leads to significant alterations in the position and anterior displacement of the hyoid bone.